ARTICLE FOR FEMINIST APPROACHES TO LINGUISTIC STUDIES. - Rayimova Shahina Shermat qizi; Roʻziboyeva Raʼno Vohidjon qizi; Abduramanova Diana Valeryevna (Ta’lim innovatsiyasi va integratsiyasi, 2024)
ABSTRACT. To generate an article on "Feminist Approaches to Linguistic Studies," you can enable our academic services. This feature allows for the creation of tailored articles, essays, and academic work.Here’s a draft outline that you might include in the article:Feminist Approaches to Linguistic Studies